Inelastic X-ray scattering experiments at extreme conditions: high temperatures and high pressures - Hosokawa, S. (Condensed Matter Physics, 2008)
In this article, we review the present status of experimental techniques under extreme conditions of high temperature
and high pressure used for inelastic X-ray scattering (IXS) experiments of liquid metals, semiconductors,
molten salts, molecular liquids, and supercritical water and methanol. For high temperature experiments,
some types of single-crystal sapphire cells were designed depending on the temperature of interest and the
sample thickness for the X-ray transmission. Single-crystal diamond X-ray windows attached to the externally
heated high-pressure vessel were used for the IXS experiment of supercritical water and methanol. Some
typical experimental results are also given, and the perspective of IXS technique under extreme conditions is
discussed. У данiй статтi ми робимо огляд сучасного стану експериментальних методик при екстремальних умовах високих температур та високих тискiв у експериментах з непружного розсiяння рентгенiвських променiв для рiдких металiв, напiвпровiдникiв, розплавiв солей, молекулярних рiдин, та надкритичних води i метанолу. Для експериментiв при високих температурах було розроблено деякi типи монокристалiчних сапфiрових комiрок, в залежностi вiд температури та ширини зразка для проходження рентгенiвських променiв. Монокристалiчнi алмазнi вiкна для рентгенiвських променiв, пiд’єднанi до комiрки, що витримує високий тиск та має зовнiшнє нагрiвання, використовувались для експериментiв по непружному розсiянню рентгенiвських променiв у надкритичних водi та метанолi. Також подано деякi типовi експериментальнi результати та обговорюється перспектива методики непружного розсiяння рентгенiвських променiв при екстремальних умовах.